Uniaxial compression performance of rectangular CFST columns with different internal construction characteristics. (1st December 2018) - Dong, Hongying; Li, Yanna; Cao, Wanlin; Qiao, Qiyun; Li, Ruijian
Highlights: Construction details of large dimensional CFST columns are given. Test samples were extracted from China Zun Tower. Six CFST columns are investigated by repeated uniaxial compression loading tests. The hysteretic behaviour, energy dissipation capacity, et al., are discussed. A bearing capacity calculation method is proposed. Abstract: To improve the compression performance and ductility of rectangular concrete-filled steel tube (CFST) columns with large dimensions, longitudinal stiffeners, horizontal tie bars, studs, internal diaphragms, and steel reinforcement cages, were set inside the columns. Six CFST column specimens with different construction characteristics were designed and tested under repeated uniaxial compression loading. Test samples were extracted from the rectangular cavities at the two ends and along the long axis of the mega-column from China Zun Tower. The hysteretic curves, skeleton curves, energy dissipation capacity, bearing capacity, stiffness and strain of specimens, and the effect on the axial compression performance based on different construction characteristics are herein discussed and clarified. Based on the conducted tests on these columns, a bearing capacity calculation method is proposed. The test results indicate that the longitudinal stiffeners set inside the CFST columns facilitate the sharing of axial forces and strengthen the stiffness, bearing capacity, and ductility. The horizontal tie bars help the improvement of the constraint of the concrete at loads higher than the ultimate load. Welding studs on the inner surface of the steel tubes help to strengthen co-operative work between the steel tubes and the concrete upon application of the ultimate load. Setting internal diaphragms inside CFST columns can enhance the ultimate bearing capacity and energy dissipation significantly. The setting of steel reinforcement cages inside the CFST columns stabilizes the mechanical performance manifested by the significant improvements in the ultimate bearing capacity and ductility.